SCHISTOSOMUS REFLEXUS W11'H PERSOMUS ACAUDATUS IN A SHE BUFFALO - CHANDRAPRASAD, B; RAJESH, M M; RAO TALLURI, THJRUMALA (The Indian Journal of Animal Reproduction, 2023)
A case of dystocia due to Schistosomus reflexus with persomus acaudatus in a Murrah she buffalo isreported.
Keywords: Buffalo; Schistosomus reflexus; Persomus acaudatus